Liquid phase collagen modified graphene that induces apoptosis. Issue 55 (17th June 2015) - Bhattacharya, Soumya; Mishra, Swati; Gupta, Pallawi; Pranav; Ghosh, Mainak; Pramanick, Ashit Kumar; Mishra, Durga Prasad; Nayar, Suprabha
<x xml:space="preserve">Abstract</x> The differential interference contrast (DIC) and fluorescence confocal micrographs show collagen microfibrils attacking graphite from all sides to form a stable dispersion of collagen modified graphene, but only collagen picks up a stain.